On the study of bright, dark and optical wave structures for the coupled fractional nonlinear Schrödinger equations in plasma physics - Badshah, Fazal; Tariq, Kalim U.; İnç, Mustafa; Aslam, Muhammad; Zeeshan, Muhammad (Springer, 2023)
The nonlinear Schrodinger equation (NLSE), one of the most fundamental physical models for understanding the fluctuations of optical soliton development, plays a significant role to demonstrate the dynamics of optical fibers. Therefore, the wave propagation in nonlinear dispersive medium is a subject of considerable interest due to the wide range of possibilities for ultrafast data processing and light pulses in communications. In this article, the coupled space-time fractional NLSE is investigated which is used to describe the non-relativistic quantum mechanical behaviour. A collection of comprehensive soliton structures are developed to study the dynamics of the governing model with the aid of some efficient analytical strategies. These solutions incorporate dark soliton and trigonometric function solutions, singular solition, dark singular solition plane wave, singular solition, opposite singular solition, smooth, bell shaped, periodic, bright, anti kink, singular bell and traveling wave with darkness. The presence of some attained solutions are flourish in 3D graphs with various fractional orders by using Mathematica. The results which we obtained reveal that the suggested approaches are more convenient and productive techniques to depict the dynamics of numerous complex wave structure in contemporary areas of science and technology.
Keywords: The coupled fractional model; Nonlinear Schrodinger equation; Analytical solutions; Optical solitons; Fractional calculus